2013
DOI: 10.1044/1092-4388(2012/10-0107)
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Talker and Intonation Variability on Speech Perception in Noise in Children With Dyslexia

Abstract: Purpose-To determine whether children with dyslexia (DYS) are more affected than agematched average readers (AR) by talker and intonation variability when perceiving speech in noise.Method-Thirty-four DYS and 25 AR children were tested on their perception of consonants in naturally-produced consonant-vowel (CV) tokens in multi-talker babble. Twelve CVs were presented for identification in four conditions varying in the degree of talker and intonation variability. Consonant place (/bi/-/di/) and voicing (/bi/-/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
6
17
2
Order By: Relevance
“…This deficit held true for the three consonant features examined here, which tempers previous finding of a specific impairment of reception of voicing and/or place of articulation in noise in dyslexic individuals (Hazan et al, 2013;Ziegler et al, 2009). Dichotic presentation of the speech target and masker minimized cochlear EM while preserving IM.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This deficit held true for the three consonant features examined here, which tempers previous finding of a specific impairment of reception of voicing and/or place of articulation in noise in dyslexic individuals (Hazan et al, 2013;Ziegler et al, 2009). Dichotic presentation of the speech target and masker minimized cochlear EM while preserving IM.…”
Section: Discussionsupporting
confidence: 84%
“…Our recent work suggests that dyslexic children experience difficulties in complex tone sequences inducing pure IM in comparison to both reading level-and age-matched controls (Calcus et al, 2015). In contrast, Messaoud-Galusi et al (2011) and Hazan et al (2013) failed to evidence a deficit in dyslexics presented with a babble noise background. Yet, as there was no attempt to remove its energetic component, the babble noise used in those two studies simultaneously induced EM and IM.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Indeed, Hayes et al reported differences between learning-disabled and normal-learning children but only when the stimuli were presented with a high level of noise. Moreover, Hazan, Messaoud-Galusi, and Rosen (2013) showed that children with dyslexia exhibited difficulties in speech-in-noise perception but only when the speaker's intonation was variable or when the listeners were under greater memory and cognitive load as in discrimination tasks. It is also possible that deficits that could emerge in the perception of words or sentences may have gone undetected in the current task with isolated nonsense syllables (e.g., Sommers, Tye-Murray, & Spehar, 2005).…”
Section: Discussionmentioning
confidence: 99%